The Effect of Implementing Nonpharmacological Interventions on Post-Caesarean Pain Management - Rusti, Aisyah Eldina; Latifah, Ahaqilla Esti (Institute of Accounting Research and Novation (IARN), 2025)
This research investigates the effect of implementing nonpharmacological interventions on post-Caesarean pain management, aiming to enhance recovery outcomes for mothers. Recognizing the limitations of conventional pharmacological approaches, this study explores various nonpharmacological strategies, including music therapy, massage, and relaxation techniques, and their impact on pain levels and emotional well-being in postpartum patients. A randomized controlled trial was conducted with a sample of postpartum women who underwent Cesarean sections, comparing those who received standard care with those who participated in nonpharmacological interventions. Results indicated a significant reduction in pain levels and improved emotional satisfaction among participants who engaged in these interventions. The findings align with previous research highlighting the effectiveness of nonpharmacological approaches in managing postoperative pain, while also identifying gaps in the literature regarding standardization and cultural influences on intervention effectiveness. This study underscores the importance of integrating nonpharmacological strategies into clinical practice, advocating for a more holistic approach to pain management that prioritizes patient comfort and satisfaction. Further research is recommended to explore the optimal combinations of interventions and their applicability across diverse patient populations.